PENGAKTUALAN UNSUR MITOLOGI DALAM PUlSl GOENAWAN MOHAMAD DAN SAPARDI DJOKO DAMONO*) - Burhan Nurgiyantoro Burhan Nurgiyantoro (Jurnal Cakrawala Pendidikan, 1999)
lndoiiesiaii literary writing today appears to containconsi-derable adoption and actualization of mythologicalstories coming fiom various parts of the country and fiomabroad. Goenawan Mo-hammad and Sapardi Djoko Damonoare the foremost Indonesian poets now considered 'pioneers"in actualizing mythological stories in poetry. A study thereforeaims at showing ( I ) the mythological elements actualizedin their poetly, (2) the forms of the hypograms of thoseelements, and (3) tlie functions of tlie actualization of thoseelements. The sources of the data for this study areGoellawan's and Sapardi's poems published in an anthol-OL3'.The result oftlie study sho\vs that mythological elementsactualized in the poelns come from various mythologies inthe country which include stories of ~~~trj.crrPiagn, ji,Anglingdatma, and Btrhutl Trrntrh./cru~ain d from those abroadwhich include stories of Iskandar Zulharnain, Serihu SuluMolarii, and classic Greece. Though relatively not many, thepoems are considered important as they reappear in laterpublications and the titles of some are even used for thosepublications. The poems containing elements of mythologicalstories as hypograms generally continue to use the conventionsof the mythology transfol~nedI.t indicates the twopoets' acceptance and response to mythology; they treat itas it is as sotilething factual. The mythological elements actualizedin the poelns are made to fuliction either as materialsto support the theme or as materials for comparison, symbolization,and cul-tural reference. Their use as support tothe theme can be regarded as offering another form ofstorytellingand their use in the other ways can be regarded asenrichment of poetical expressions.